Dental anxiety before the first step and after the second step of periodontitis therapy - Sanabria Bogantes, Daniela (2023)
Introduction: individuals that experience Dental Anxiety (DA) may avoid dental appointments and even postpone treatments, including periodontal treatment. The aim of this study was to 1) determine DA in patients with periodontitis before the first step and after the se cond step of periodontitis therapy (non surgical periodontal treatment), and 2) collect sociodemographic and clinical characteristics of the studied population. Methods: patients with periodontitis that had never received subgingival instrumentation and attended the Clinic of Periodontics of the Facultad de Odontología, Universidad de Costa Rica, were invited to participate. From the electronic dental record, the following information was obta ined: periodontal staging, Plaque Index (PI) and Gingival Bleeding Index (GBI). A questionnaire was applied before the first step and after the second step of periodontitis therapy. Data collected included: sociodemographic factors, smoking habits, ex smoker status, pain, and the Modified Corah Dental Anxiety Scale (MDAS). Results: fifty one patients completed the study, 19 men and 32 women, mean age 46 ±11.16 years. Most of the participants reported having com pleted high school. Regarding smoking habits, 46% were non smokers. Of the non smokers, 7.8% were former smokers. Patient’s maxim al pain in the last month decreased after the completion periodontitis therapy. The most prevalent periodontal diagnosis was Stage III followed by Stage II. The average PI was 61.4% and the average GBI was 39.5%. Fear to the sound of rotatory instruments/u ltrasonic scalers ameliorated after completion of therapy. Total MDAS score and sub scores decreased from baseline. Conclusion: self perceptions of DA improved over the course of periodontal treatment in our clinical setting.